2009
DOI: 10.1111/j.1749-6632.2009.04747.x
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Mechanisms of Atherogenesis

Abstract: The concept that atherosclerosis is an autoimmune disease is no longer controversial. Attention has been paid to cellular immune response, but current research is now focused on the humoral component of this complex disease. Heat shock proteins, oxidized low-density lipoproteins, beta2-glycoprotein 1, cardiolipins, and, more recently, high-density lipoproteins have been considered to be autoantigens that play a part in atherogenesis. The characterization and understanding of the mechanisms associated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 72 publications
(127 reference statements)
0
3
0
Order By: Relevance
“…Our finding agrees with the suggestion that higher estrogen levels usually associate with the production of auto-antibodies. 74,75 The results of our study demonstrated sex hormones and prolactin levels and metabolism are different in female SLE patients compared to healthy subjects. It seems, low serum levels of testosterone, DHEA-S and progesterone and high serum levels of estradiol and prolactin could be related to higher SLE disease activity, increase of thrombotic risks and higher renal complications.…”
Section: Discussionmentioning
confidence: 69%
“…Our finding agrees with the suggestion that higher estrogen levels usually associate with the production of auto-antibodies. 74,75 The results of our study demonstrated sex hormones and prolactin levels and metabolism are different in female SLE patients compared to healthy subjects. It seems, low serum levels of testosterone, DHEA-S and progesterone and high serum levels of estradiol and prolactin could be related to higher SLE disease activity, increase of thrombotic risks and higher renal complications.…”
Section: Discussionmentioning
confidence: 69%
“…This result partially disagrees with the notion that higher estrogen levels usually associate with the production of autoantibodies. 12 This observation is relevant, considering that both estrogen defi ciency and ACA are related to the risk for atherosclerotic disease. So far, the association between hypoestrogenism and the presence of ACA in premenopausal women with SLE has not been described.…”
Section: Discussionmentioning
confidence: 99%
“…12,16 A study published in 2008 17 investigated the in vitro effect of estrogen on apoptosis of endothelial cells in culture, demonstrating that estrogen inhibits, although incompletely, apoptosis induced by TNF-α and oxidized LDL. Thus, a possible explanation for the association of low estradiol levels and the presence of ACA would be the increased activation of endothelial apoptosis caused by the low endogenous estrogen levels, leading to increased exposure to endothelial and even subendothelial antigens, such as oxidized LDL.…”
Section: Discussionmentioning
confidence: 99%